Pengaruh Variasi Komposisi Aditif PEG Terhadap Kinerja Membran CA - Al-Fitri, Mahriandhanie Chika; Pinem, Jhon Armedi; HS, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The membrane is defined as a selective and semipermeable thin layer between two phases, namely the feed phase and the permeate phase. The purpose of this study is to make cellulose acetate from pineapple leaves, make cellulose acetate membrane with variations in the composition of PEG additives, and study the effect of PEG additive composition on the characteristics of cellulose acetate membranes produced. The methodology in this research is isolation of cellulose from pineapple leaves, synthesis of cellulose acetate from pineapple leaf fibers, synthesis of cellulose acetate membrane, pre-treatment of pulp and paper industry wastewater, and characterization of cellulose acetate membrane. The variation in the composition of the additives Polyethylene Glycol (PEG) used is 5, 10, 15 % w/w. Pulp and paper industrial wastewater treatment using cellulose acetate membrane is carried out with a variation of 2 bar operating pressure. The highest value of flux was obtained on membranes with a composition of PEG 15% w/w that is 39.922 L/m2.hour. The highest value of the rejection of COD, BOD5 and TSS parameters were obtained from the membrane with a PEG composition of 5% w/w, that are 67.13%; 76.45% and 74.42%. Keywords: membrane, polyethylene glycol (PEG), cellulose acetate